Evaluation of resistance of corn hybrids against the attack of Sitophilus zeamais motschulsky (Coleoptera: Curculionidae) in stored kernels - Marsaro Júnior, Alberto Luiz; Lazzari, Sonia Maria Noemberg; Kadozawa, Patrícia; Hirooka, Elisa Yoko; Gerage, Antônio Carlos (Semina: Ciências Agrárias, 2005)
Resistance of corn hybrids, cultivated or in phase of genetic improvement in Paraná, was evaluated against the attack of Sitophilus zeamais, main grain pest of corn storage. Samples of kernels of eleven hybrids of corn, IPD T1/3AC, IPD 029, IPT 4/029, AG 5011, IPS G/58, IPT 2/15, IPT 4/15, IPT T/23, IPT 5/T02, IPT 2/92 and IPT 9/13, were infested with adults of S. zeamais and maintained in BOD, at 27Â±1Â°C, 75Â±5% RH and 12 hours of photophase. After 30 days of infestation the following parameters of resistance were evaluated: susceptibility index, reduce of dry mass of the grains, number of emerged insects, biological cycle and adult mass. The most susceptible hybrids to the attack of S. zeamais were: IPD T1/3AC and IPD 029; while the most resistant were: IPT 4/029, AG 5011, IPS G/58, IPT 2/15 and IPT 4/15.